School-based strategies for implementing psychoeducation on emotion regulation in junior high students - Aryani, Mirsa; Adhitama, Muhammad Fachri; Syifa, Fitriana Aulia; Meitarizky, Alifia Rahma; Shadrina, Aisyah Zharfa Nur; Aini, Dewi Khurun (Universitas Muhammadiyah Magelang, 2025)
Adolescence is a period when individuals undergo numerous changes, including physical, psychological, and emotional shifts. Many issues arise during this stage due to adolescents' inability to regulate their emotions. Therefore, this project was conducted with the goal of enhancing adolescents' emotion regulation abilities. The study involved 36 participants ranging in age from 13 to 15 years old. The participants were students from Junior High School Hasanuddin 06 Semarang, Indonesia. The activities were performed using a conventional approach that focused on interaction between the presenter and the audience. It incorporated active learning methods, specifically interactive question-and-answer sessions and discussions. Data during study was analysed by using Paired T-test. The research results show that there is an increase in knowledge about emotion regulations among the junior high school student population (p<0.05). This finding demonstrates that the psychoeducation increased the students' knowledge and understanding of emotion and how to regulate emotions. Therefore, the results of this program can serve as a foundation for psychologists to use psychoeducation as an innovation or approach to address emotional regulation issues, particularly among adolescents. Keywords: Behavioural science, emotional regulation, psychoeducation, psychological issues, teenagers